2017
DOI: 10.2147/ahmt.s70377
|View full text |Cite
|
Sign up to set email alerts
|

Targeted therapy for soft tissue sarcomas in adolescents and young adults

Abstract: Soft tissue sarcomas (STSs) are a heterogeneous group of tumors originating from the mesenchyme. Even though they affect individuals in all age groups, the prevalence of subtypes of STSs changes significantly from childhood through adolescence into adulthood. The mainstay of therapy is surgery, with or without the addition of chemotherapy and/or radiation therapy. These treatment modalities are associated, in many cases, with significant morbidity and, given the heterogeneity of tumor histologies encompassed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 178 publications
(153 reference statements)
0
13
0
Order By: Relevance
“…‘Precision medicine’ or molecular targeting of cancer cells aims at delivering drugs to specific cancer genes or proteins to increase effectiveness and decrease the toxicity of therapy. However, in the absence of clinical trials, it can be unclear if response to therapy is the same in AYA as in adults and may be worse . Furthermore, the relationship of dose to activity at the cancer cell is unknown in AYA, as are the off‐target effects.…”
Section: New Issues For Considerationmentioning
confidence: 99%
See 2 more Smart Citations
“…‘Precision medicine’ or molecular targeting of cancer cells aims at delivering drugs to specific cancer genes or proteins to increase effectiveness and decrease the toxicity of therapy. However, in the absence of clinical trials, it can be unclear if response to therapy is the same in AYA as in adults and may be worse . Furthermore, the relationship of dose to activity at the cancer cell is unknown in AYA, as are the off‐target effects.…”
Section: New Issues For Considerationmentioning
confidence: 99%
“…Mental health issues are on the rise for young people, both in Australia and around the world. 12,13 The Mission Australia Youth Health report demonstrated a rise in the number of [15][16][17][18][19] year olds who met the criteria for a serious mental illness from 18.7% in 2012 to 22.8% in 2016. 12 The second Australian Child and Adolescent Survey of Mental Health and Wellbeing survey demonstrated that 14% of children and adolescents had mental health problems, and 16.7% of those young people with a mental health issue were taking medication.…”
Section: Mental Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Because treatment protocols are increasingly focused on precise diagnosis for soft tissue tumors/sarcomas, broad molecular profiling of pediatric malignancies will become ever more critical as a diagnostic tool. 15 In addition to improved diagnosis, routine application of the OncoKids panel can improve therapy by identifying targetable mutations in the front-line setting. Of note, imatinib has been incorporated into current treatment algorithms for Philadelphia (Ph) chromosomeepositive acute lymphoblastic leukemia (ALL).…”
mentioning
confidence: 99%
“…They arise from the tissues that emerge from the embryonic mesoderm and therefore are all mesenchymal. The WHO defines STSs as soft tissue tumors with malignant potential, that is, a propensity for locally destructive growth, risk of recurrence, and risk of distant metastasis ( 1 , 2 ).…”
mentioning
confidence: 99%